1999
DOI: 10.1002/(sici)1097-0215(19990719)82:2<268::aid-ijc18>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinase (MAPK) regulates the expression of progelatinase B (MMP-9) in breast epithelial cells

Abstract: Mitogen‐activated protein kinases (MAPKs) play a major role in the mitogenic signal transduction pathway and are essential components of both growth and differentiation. Constitutive activation of the MAPK cascade is associated with the carcinogenesis and metastasis of human breast and renal cell carcinomas. The gelatinases B (MMP‐9) and A (MMP‐2) are 2 members of the matrix metalloproteinase (MMPs) family which are expressed in human cancers and thought to play a critical role in tumor cell invasion and metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(84 citation statements)
references
References 23 publications
7
73
1
3
Order By: Relevance
“…Although the present data and other reports 25,26,31,34,48 strongly suggest a role for MAPKs in MMP-9 regulation, involvement of PI3K in growth factor-induced MMP-9 production has not been extensively studied. Blocking of PI3K by selective inhibitors effectively inhibited BTC-enhanced MMP-9 expression in HNSCC cells, indicating that PI3K is required for this process.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Although the present data and other reports 25,26,31,34,48 strongly suggest a role for MAPKs in MMP-9 regulation, involvement of PI3K in growth factor-induced MMP-9 production has not been extensively studied. Blocking of PI3K by selective inhibitors effectively inhibited BTC-enhanced MMP-9 expression in HNSCC cells, indicating that PI3K is required for this process.…”
Section: Discussioncontrasting
confidence: 70%
“…Blocking of PI3K by selective inhibitors effectively inhibited BTC-enhanced MMP-9 expression in HNSCC cells, indicating that PI3K is required for this process. Reddy et al 48 reported that PI3K inhibition only partially blocked EGF induction of MMP-9 expression in mammary carcinoma cells, whereas both invasion and MMP-9 production were significantly dependent on MEK signaling. In contrast, roles for PI3K pathways in both basal and EGF-stimulated in vitro invasion and MMP-9 expression in ovarian cancer cells have been suggested, 27 as observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published data shows that ERK1 and ERK2 are speci®cally activated by MEK1 because of its ability to promote both threonine and tyrosine phosphorylation of these (Cowley et al, 1994;Zheng and Guan, 1994). In addition, there is data from our group using SKBR-3 cells (Reddy et al, 1999b) and also other groups using keratinocytes suggesting growth factors that can induce sustained MAPK activation enhances cell migration and invasion (McCawley et al, 1999;Zeigler et al, 1999). To test the hypothesis that MAPK activation enhances cell motility and invasion in non-invasive cells, we stably expressed a constitutively activated MEK1 in non-invasive MCF-7 cells (MEK/MCF-7 cells) and examined its e ect on cell migratory and invasive properties.…”
Section: Mapk Activation Is Critical For Cell Migration But Not Suffimentioning
confidence: 99%
“…These studies have provided evidence that certain receptor kinases such as EGFR, ERB2, PDGF and others are involved in tumor development (Heldin and Ostman, 1996;McCawley et al, 1999;Reddy et al, 1999b). These growth factors have been shown to stimulate cell migration by activating receptor tyrosine kinase activity, leading to activation of the Ras/ MAPK signal pathways (Hartmann et al, 1994;Klemke et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Hellmich et al [23] found that bombesin induced either intracellular calcium oscillations or biphasic elevation in intracellular calcium, and that the activation of mitogen-activated protein kinase (MAPK) kinase (MEK) was important for maintaining the elevated intracellular calcium levels induced by bombesin. The MAPK-MEK cascade was closely related to the tumor cell invasion [24]. However, we did not examine the intracellular calcium level induced by bombesin in this animal model.…”
Section: Discussionmentioning
confidence: 94%